Experimental study of noise and back pressure for silencer design characteristics - Mohiuddin, A. K. M.; Ideres, Mohd Rashidin; Mohd Hashim, Shukri (Asian Network for Scientific Information, 2005)
The main objective of this study is to find the relationship between the back pressure and the noise level. Back pressure needs to be kept to a minimum. The relationship between the noise and the back pressure is inversely proportional; lowering the noise level at the tip will result in high back pressure. However, this relationship is undesirable as the requirement is to have a quiet muffler with a small back pressure (ideal muffler). The design of the muffler chamber separation and arrangement is essential in determining the muffler characteristics. Some design considerations are proposed in order to come up with an optimum muffler design. The results how a general shape of an average design of the muffler which would be the most suitable for the test car model.